Utilization of Green Bean Juice (Vigna Radiata) Added with Cinnamon Powder (Cinnamomum Burmanii) in Lowering Cholesterol Levels in Hypercholesterolemia Sufferers - Dian Eka Maulida; Retno Wahyu Ningsih; Ni Ketut Sri Sulendri; Joyeti Darni (Jurnal Gizi Prima (Prime Nutrition Journal), 2024)
Background: Elevated cholesterol levels are a risk factor for cardiovascular disease, overweight/obesity, and stroke, which has a predicted death rate of around 2.6 million worldwide. One way to reduce cholesterol levels is to regulate the consumption of foods containing fat (saturated, trans, cholesterol), exercise regularly, and choose foods with a high isoflavone content, for example, green beans.Research Methods: The research method uses a quasi-experiment and a non-equivalent control group design. The research used 20 subjects, 10 of whom were treated and 10 of whom were controls. This study also considered data on fat and fiber intake. Intake data was collected twice before and during the research using the food recall method. The independent T-test was used to determine the product's effect on reducing cholesterol levels.Research Result: The results showed differences in cholesterol levels before and after the study (p=0.00). The treatment group had a reduced cholesterol level of 57.8 mg/dL, and the control group had a reduced cholesterol level of 34.3 mg/dL. However, the benefits of green bean juice with cinnamon powder in lowering cholesterol levels were not statistically significant (p=0.074).Conclusion: Drinking green bean juice with the addition of cinnamon powder has not been statistically proven to reduce cholesterol levels.